2018
DOI: 10.1002/jrs.5474
|View full text |Cite
|
Sign up to set email alerts
|

High vibrational overtone excitation‐induced conformational isomerization of glycolic acid in solid argon matrix

Abstract: The high overtone‐induced isomerization of glycolic acid in a low‐temperature argon matrix was investigated using Raman spectroscopy. The Raman spectrum of glycolic acid is presented, and the spectral assignment is supported by vibrational anharmonic calculations. The high overtone excitation of the lowest energy conformer (SSC) at 532 nm induced direct conformational isomerization to higher energy conformers (GAC and AAT). Furthermore, upon excitation at 532 nm GAC and AAT isomerized back to SSC and photo‐ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Ahokas et al described their study on high vibrational overtone excitation‐induced conformational isomerization of glycolic acid in solid argon matrix . Brambilla and co‐workers synthesized regio‐regular poly(3‐hexylthiophene‐2,5‐diyl) selectively deuterated on the main chain backbone and/or on the hexyl side chain giving the opportunity to record IR and Raman spectra and to carry out a spectroscopic study supported by density functional theory calculations .…”
Section: Vibrational Studies In Chemistrymentioning
confidence: 99%
“…Ahokas et al described their study on high vibrational overtone excitation‐induced conformational isomerization of glycolic acid in solid argon matrix . Brambilla and co‐workers synthesized regio‐regular poly(3‐hexylthiophene‐2,5‐diyl) selectively deuterated on the main chain backbone and/or on the hexyl side chain giving the opportunity to record IR and Raman spectra and to carry out a spectroscopic study supported by density functional theory calculations .…”
Section: Vibrational Studies In Chemistrymentioning
confidence: 99%
“…Experimental IR positions of SSC νOH A and νOH C is 3561.0; GAC: νOH A 3648.0; νOH C 3563.0; AAT: νOH A 3670.0; νOH C 3473.0 cm −1 . Experimental Raman spectra positions of SSC νOH A and νOH C is 3566.0; GAC: νOH A 3652.0, νOH C 3568.0; AAT: νOH A 3675.0, νOH C 3478.0 cm −1 [12].…”
Section: Figurementioning
confidence: 99%
“…The concept of near-infrared photochemistry was suggested by Donaldson et al [1], for example, to describe OH-containing species such as HONO, HNO 3 , carboxylic acid, or alcohols absorbing NIR or visible radiation via vibrational overtones of the OH stretching mode that induced rotamerisation or even dissociation of the molecule. Up-to-now, the majority of overtone excitation studies has been reported for carboxylic acids [4,5,6,7,8,9,10,11,12,13]. As follows, glycolic acid (GA), the smallest α-hydroxycarboxylic acid, is also an advantageous object for such studies due to the presence of two hydroxyl groups with different surroundings in the same molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, GA is a model species to study in order to understand how competing OH-groups in the molecule affect the chemical reactivity and capability to form molecular complexes. Several reports on monomeric GA isolated in low-temperature matrices as well as its transformations have appeared in the literature [15,16,17,18,19,20]. The structures of the three most stable GA species are presented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%